Strategy and force planning : the case of the Persian Gulf - Epstein, Joshua M. (Washington, D.C. : The Brookings Institution, 1987)
In this book, the author sets forth the three basic strategies available to the United States for the deterrence of Soviet conventional aggression and determines which of these strategies would prove most credible in the Persian Gulf region. His purpose is to address a defense policy problem of immediate concern to the United States, while shedding light on enduring theoretical questions of strategic choice and the determination of military requirements.
Includes index.
Includes bibliographical references: p. 156-165.
ne 17/05/2018
Loans
Keywords: Persian Gulf Region--Defenses.; United States--Military relations--Persian Gulf Region; Persian Gulf Region--Military relations--United States; Persian Gulf Region--Military relations--Soviet Union; Persian Gulf Region; United States; Soviet Union